1983
DOI: 10.2307/1599514
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Violence: A Study of Intersexual Homicide in Chicago

Abstract: 2 See FEDERAL BuREAu OF INVESTIGATION, U.S. DEP'T OF JUSTICE, UNIFORM CRIME REPORTS (1958-1982) [hereinafter cited as UNIFORM CRIME REPORTS]. (The Federal Bureau of Investigation ("FBI") publishes its Uniform Crime Reports annually. The dates given hereinafter in citations refer to the year for which the data were collected. The Uniform Crime Reports generally is released during the year following data collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Gillis (1986) analyzed published data from 1961-1974 and found that the proportion of domestic homicides decreased in relation to all homicides. Zimring et al (1983) found a similar pattern in U.S. data. Table I extends Gillis' data 7 years for Canadian cases.…”
Section: Methodssupporting
confidence: 71%
See 3 more Smart Citations
“…Gillis (1986) analyzed published data from 1961-1974 and found that the proportion of domestic homicides decreased in relation to all homicides. Zimring et al (1983) found a similar pattern in U.S. data. Table I extends Gillis' data 7 years for Canadian cases.…”
Section: Methodssupporting
confidence: 71%
“…The domestic-stable category had the lowest rate of homicide by far (0.0494 per thousand). This may echo the suggestion of Zimring et al (1983) that marriage acts as a kind of "life insurance" given the rarity of homicide in this relationship. The domestic-unstable group had a rate more than three times that of the domestic-stable category (0.1712 per thousand).…”
Section: Rates Of Intimate Homicidementioning
confidence: 67%
See 2 more Smart Citations
“…Among studies that examine specific jurisdictions, findings indicate that the majority of victims and offenders are acquaintances or strangers. For example, Zimring, Mukherjee, and van Winkle (1983) found that only 9% of the homicides in Chicago were among intimate partners or family members whereas nearly 83% were designated as intrasexual homicides (e.g., strangers and undetermined relationships). Additionally, medical examiner records in Florida indicated that over half (56%) of the homicide cases were committed by acquaintances and strangers compared to primary victim-offender relationships (Drawdy & Myers, 2004).…”
Section: Victim-offender Relationshipmentioning
confidence: 99%